2016
DOI: 10.1093/ajh/hpw108
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension in Middle-Age and Risk of Falls

Abstract: Falls are a major cause of morbidity and mortality among older adults. 1,2 Nearly, one-third of persons aged 65 or older falls each year and the rate of falls in the United States is rising. 1,2 Moreover, falls are a significant reason for emergency room visits 3 and predispose to the risk of fracture, 4 posing a substantial burden on the US health system, estimated at approximately $23 billion yearly. 5 Given the aging US population, identifying risk factors for falls and tailoring interventions (e.g., physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 53 publications
0
80
1
4
Order By: Relevance
“…[26][27][28] Juraschek et al reported that orthostatic hypotension in middle-aged adults was positively associated with falls, fractures, and syncope during a median of 23 years of followup. 29 Finucane et al also found a 40% increased risk of falls at 2 years of follow-up in people with orthostatic hypotension in a population-based prospective study in Irish adults. 30 The SPRINT study also supported this finding, 31 as did smaller and cross-sectional studies, 28,32 although one moderately large prospective study did not.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[26][27][28] Juraschek et al reported that orthostatic hypotension in middle-aged adults was positively associated with falls, fractures, and syncope during a median of 23 years of followup. 29 Finucane et al also found a 40% increased risk of falls at 2 years of follow-up in people with orthostatic hypotension in a population-based prospective study in Irish adults. 30 The SPRINT study also supported this finding, 31 as did smaller and cross-sectional studies, 28,32 although one moderately large prospective study did not.…”
Section: Discussionmentioning
confidence: 91%
“…Orthostatic hypotension (a drop in BP on standing), which becomes more prevalent with aging and is more common in individuals with hypertension, might be another link between antihypertensive treatment and falls . Juraschek et al reported that orthostatic hypotension in middle‐aged adults was positively associated with falls, fractures, and syncope during a median of 23 years of follow‐up . Finucane et al also found a 40% increased risk of falls at 2 years of follow‐up in people with orthostatic hypotension in a population‐based prospective study in Irish adults .…”
Section: Discussionmentioning
confidence: 91%
“…Precise measures of postural hypotension using beat-to-beat blood pressure monitoring techniques have recently provided unique insight into the relationship between postural hypotension and falls. 16,17 Future work examining nerve conduction velocity and continuous beat-to-beat monitoring assessments of postural hypotension may be an important extension of this work, particularly as both have been related to falls in older adults. 9,12,1618 Two of our measures of cardiovascular autonomic function were dependent on completing a 400m endurance walking test—the Long Distance Corridor Walk.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Covariates were selected a priori to examine the independent association between OH and CVD 28, 29, 31. We specifically examined established cardiovascular risk factors on the basis of demographic information, self‐reported behaviors, body mass index, cholesterol, and comorbid conditions (diabetes mellitus, hypertension, and chronic kidney disease).…”
Section: Methodsmentioning
confidence: 99%